Comprehensive patent data of the German Democratic Republic 1949-1990 - Ann Hipp; Michael Fritsch; Maria Greve; Jutta Günther; Marcel Lange; Christian Liutik; Beate Pfeifer; Mariia Shkolnykova; Michael Wyrwich (Journal of Economics and Statistics, 2024)
We document the generation and the content of the Comprehensive Patent Database (CPDB) of the German Democratic Republic (GDR) (1949-1990), which is freely available at GESIS https://doi.org/10.7802/2448. The database contains all patents granted in the GDR and published by the Office of Inventions and Patents (later: German Patent and Trade Mark Office/DPMA). The core database covers the years 1950-1990 and contains 24 variables with manually cleaned and processed information on a total of 261,822 unique patents of the GDR.
Keywords: O31; O33; P29; P39; B24; 330; German Democratic Republic (GDR); invention; patent data